The Dispute on State Institutions' Authority: An Analysis from the Newmont Divestment Case - Syahra Ramadhani; Maynanda Shadrina; Sholahuddin Al-Fatih (Faculty of Law, University of Jember, Indonesia, 2021)
It is argued that Indonesia has three main institutional functions, inter alia, executive, legislative, and judiciary. They are interlinked as constitutional organs due to their respective positions and functions. In this context, the inter-state institutions have a supervisory body that controls other institutions due to checks balances. As a result, it can lead to disputes among them, usually related to constitutional authority discourse. This paper analyzed the differences in implementing the existing laws governing an institutional power and function that encouraged disputes by taking the Newmont divestment case as an example. This paper's method was juridical research, with statutory, case, and conceptual approaches. The paper showed that state institutions inter alia, the President, the House of Representatives, and the Financial Audit Agency, shared the same authority to resolve the Newmont divestment case. The complexity of this case involved many parties, which dealt with the contention of the purchase of 7% shares of Newmont Nusa Tenggara Company. Consequently, this case was resolved and decided in the Constitutional Court with disputes over state institutions' authorities. This paper recommended a further elaboration on the limits and meanings of state institutions. KEYWORDS: Constitutional Disputes, State Institutions, Newmont Divestment.